Expert : intensive training, intensive practice, be an expert - Fiona Aish; Jo Tomlinson; Rose Aravanis (Essex : Pearson Education, 2017)
"Expert IELTS is an intensive course for students preparing for the International English Language Testing System (IELTS). Expert IELTS trains students in all parts of the IELTS test, improving their scores and building language proficiency. It helps students stay focused to get the IELTS band score they need to achieve their goals, whether it's to get a better job, get on to a university course or for visa requirements. The Expert IELTS teacher's resource book provides essential support to teach the course. It gives you clear guidance on how to make the most of the coursebook material and how to use the other resources and compnents to personalise learning for classes and individuals"--Page 4 of cover
Keywords: English language Examinations Study and teaching; International English Language Testing System Study and teaching; English language Study and teaching